Peningkatan Motivasi Belajar Materi Haji, Zakat dan Wakaf Melalui Problem Based Learning Kelas X SMA Negeri 4 Tambusai Utara - Nurulazmi, Nurulazmi; Sugiat, Sugiat (Tematik: Jurnal Penelitian Pendidikan Dasar, 2024)
Mathematics plays a crucial role in fostering logical reasoning, analytical thinking, and problem-solving skills essential for various scientific disciplines. However, many students perceive mathematics as a challenging subject, highlighting the need for effective pedagogical approaches rooted in established learning theories. This study examines the development of learning theories—behaviorism, cognitivism, constructivism, and social learning—and their applications in mathematics education while proposing strategies for effective instruction. Employing a qualitative literature review approach, this research synthesizes data from various academic sources. The findings reveal that each learning theory offers distinct advantages: behaviorism is effective for skill acquisition and reinforcement, cognitivism enhances conceptual understanding, constructivism facilitates knowledge construction through active engagement, and social learning theory underscores the significance of interaction and collaboration. The study advocates for an integrative approach that combines multiple learning theories to improve students’ comprehension, motivation, and engagement in mathematics. Furthermore, it emphasizes the necessity of continuous teacher training to ensure the effective implementation of these theories in the classroom, ultimately fostering a more interactive and student-centered learning environment.